Modelling of heat processes during the surface treatment of inhomogeneous metal bodies by a high-temperature moving pulse source - Bagmutov, Vyacheslav Petrovich; Zakharov, Igor Nikolaevich (Computational Continuum Mechanics, 2011)
A mathematical model capable of describing the thermal action of concentrated energy fluxes on inhomogeneous metal bodies subjected to electromechanical treatment (EMT) is developed. The peculiarities of formulation and solution of a three-dimensional heat conduction problem under high-speed heating and cooling conditions, including the description of the spatial and time configurations of a moving pulse heat source and the account of the latent heat of phase transformations and the temperature dependence of the thermophysical characteristics of a body in specific structural areas, are considered. The obtained numerical results allowed us to study the temperature distribution mechanisms and the rate of temperature change caused by the action of the moving pulse source on the steel sample with a surface layer or covering subjected to EMT. It is shown that a consideration of the temperature dependence of thermophysical coefficients leads to quantitative and qualitative changes in the distribution of temperature and its gradients. Application of a hyperbolic heat conduction equation to the analysis of the EMT processes provides only an inessential refinement of the problem solution.
Keywords: computer modelling; thermal processes; concentrated energy fluxes; electromechanical treatment